2015
DOI: 10.1016/j.envres.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in mortality risk for hematological malignancies near a petrochemical refinery: A population-based case-control study

Abstract: Introduction The study investigated the geographic variation of mortality risk for hematological malignancies (HMs) in order to identify potential high-risk areas near an Italian petrochemical refinery. Material and methods A population-based case-control study was conducted and residential histories for 171 cases and 338 sex- and age-matched controls were collected. Confounding factors were obtained from interviews with consenting relatives for 109 HM deaths and 267 controls. To produce risk mortality maps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Two comprehensive studies have reviewed associations between proximity to petrochemical industrial areas and adverse health outcomes. , Most published studies have found a higher cancer incidence and mortality, with the leading associated cancers being leukemias and respiratory tract (mainly lung) cancers. Other studies found associations with cancer of the liver, pancreas, brain, , bladder, ,, and various hematological malignancies. , Studies that assessed the association with any cancer (regardless of the cancer site) also found positive associations. However, many of these investigations are limited by low statistical power given the few cases of each specific cancer. Another common limitation is the ecological design, which almost always lacks a detailed exposure assessment and is prone to residual confounding.…”
Section: Introductionmentioning
confidence: 99%
“…Two comprehensive studies have reviewed associations between proximity to petrochemical industrial areas and adverse health outcomes. , Most published studies have found a higher cancer incidence and mortality, with the leading associated cancers being leukemias and respiratory tract (mainly lung) cancers. Other studies found associations with cancer of the liver, pancreas, brain, , bladder, ,, and various hematological malignancies. , Studies that assessed the association with any cancer (regardless of the cancer site) also found positive associations. However, many of these investigations are limited by low statistical power given the few cases of each specific cancer. Another common limitation is the ecological design, which almost always lacks a detailed exposure assessment and is prone to residual confounding.…”
Section: Introductionmentioning
confidence: 99%